Preparation and in Vitro Evaluation of Soya Lecithin Based Nano Transfersomal Dispersion for Loxoprofen Sodium - Huda S. Kadhium; Nidhal K Maraie (College of Pharmacy / Mustansiriyah University, 2019)
This work involves investigation and evaluation of the factors that affect the preparation and release of the model class I drug (loxoprofen sodium) to optimize the efficiency of its prepared nano transfersomal dispersion to give rapid onset of action (burst effect) within the   first 2 hours that can continue for further four hours. The work involved preparation of twenty formulas of transfersomal dispersion by thin film method which were nano-sized by probe sonication and characterized morphologically by Transmission electronic microscopic (TEM), zeta potential, particle size, polydispersity index (pdI), pH, physical appearance, entrapment efficiency, viscosity, transmittance and in vitro drug release. The selected nano transfersomal formula (SF16) showed pH (7.2), particle size (393 nm), pdI (0.259), zeta potential (-25), entrapment efficiency (91%) and gave a 73% drug release within the first 2 hours of the in vitro test and continued until it gave 86.35% drug release after 4 h. This work succeeded in preparing optimized tansfersomal dispersion for loxoprofen sodium using different soya lecithin / edge activator percent and different types of edge activator. The optimum formula gave an immediate release of the model drug (loxoprofen sodium) and it was ready to be incorporated in any suitable dosage form to give continuous drug release.